Stunting prevention movement through socialization with IPNU and IPPNU youth, Tengki Village, Brebes District, Brebes Regency - M. Zidny Nafi' Hasbi (Business Finence Analyst Co.,, 2024)
Stunting is a condition of growth failure in children occurs due to chronic malnutrition for a long period of time, thus inhibiting growth and development. In this study we used an observation method where we went directly to the field with health workers to see how conditions were in the community of Tengki Village, Brebes. Pupolation and samples in this study were all tengki residents. Efforts to prevent stunting that can be done are to meet nutritional intake from egg fertilization to children aged 2 years, provide exclusive breastfeeding until the baby is 6 months old, and strive for children to get complete immunization. The conclusion of this study is that stunting prevention in the Tengki Village area of Brebes Regency can be carried out through the observation and socialization stages. This activity started from observations made by all members of KKNT group 6 of Tengki Village, Brebes Regency, Counseling activities on stunting prevention attended by 50% of Tengki Village adolescents and Education Additional feeding was given 80% by the people of Tengki Village.